Fabrication and characterization of screen printed NiMn2O4 spinel based thermistors. Issue 2 (28th January 2022) - Uppuluri, Kiranmai; Szwagierczak, Dorota
Abstract : Purpose: The purpose of this work was to characterize NiMn2 O4 spinel-based thermistor powder, to use it in screen printing technology to fabricate temperature sensors, to study their performance for different sintering temperatures of thermistor layer, with and without insulative cover, as well as to investigate stability of the fabricated thermistors and their applicability in water quality monitoring. Design/methodology/approach: After the characterization of starting NiMn2 O4 spinel-based thermistor powder, it was converted to thick film paste which was screen printed on alumina substrate. Thermistor layers were sintered at four different sintering temperatures: 980°C, 1050°C, 1150°C and 1290°C. An interdigitated pattern of Ag-Pd conductive layer was used to reduce the resistance. Temperature-resistance characteristics were investigated in air and water, with and without insulative cover atop the thermistor layer. Stability of the fabricated thermistors after aging at 120°C for 300 h was also examined. Findings: Thick film NiMn2 O4 spinel thermistors, prepared by screen printing and sintering in the temperature range 980°C–1290°C, exhibited good negative temperature coefficient (NTC) characteristics in the temperature range −30°C to 145°C, including high temperature coefficient of resistance, good stability and applicability in water. Originality/value: This study explores the range of sintering temperature that can be applied for NiMn2 O4 thermistor thick films without compromising on the temperature sensing performance in air and water, as well as stability of the thermistors after aging at elevated temperatures.